Paltelet Count To Spleen Diameter Ratio As a Predictor of Esophageal Varices In Choronic Liver Diseases Due To Hepatitis C (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the diagnostic accuracy of platelet, count to spleen diameter ratio for presence of oesophageal varices in patients of chronic liver disease secondary to Hepatitis C taking endoscopy as gold standard.Material and Methods: The design of this study was cross sectional study. This study was carried out in Department of Medicine DHQ Hospital Mirpur and the duration of this study were 6 months from January 2024 to June 2024. The sampling technique of this study was non-probability consecutive sampling.  After informed consent from patients, 180 patients fulfilling clinical case definition of CLD secondary to Hepatitis C were included in the study. Upper GIT endoscopy was done by standard protocol and oesophageal varices having a size of more than or equal to 5 millimetre (mm) were considered positive. The platelet counts in number per micro litre (µl) was measured by doing complete blood count (CBC) and the spleen diameter in millimetre was measured by doing abdominal ultrasonography (USG).Results: The study population consisted of 180 patients of CLD secondary to HCV. Mean age of patients was 50.76±12.872 years. There were 86 (47.8%) male and 94 (52.2%) females, out of 180 patients. On Upper GIT endoscopy, the EVs were present in 95 (52.8%) and 85 (47.2%) patients have no EVs. The mean of PC/SD ratio of patients with varices was 831.0287 and those of without varices was 1358.4154. The mean of PC/SD ratio of all the patients was 1080.0724. The sensitivity and specificity for the diagnostic accuracy of PC/SD ratio were 71.6% and 58.8% respectively. The positive predictive value and negative predictive value were 66.0% and 64.9% respectively. The diagnostic accuracy of PC/SD ratio for prediction of EVs was 65.6%.Conclusion: The PC/SD ratio is non-significantly associated with prediction of esophageal varices having a diagnostic accuracy of 65.6%.